Manajemen Hemodinamik Menggunakan Electrical Cardiometry (EC) dengan Mempertimbangkan Parameter Makrosirkulasi dan Mikrosirkulasi - Sudadi; Mahmud; Rani, Hajar Rafika (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2020)
A 62-year-old woman with peritonitis suspected of intestinal perforation who underwent exploratory laparotomy. Patients with ASA 2 physical status with geriatrics, leukocytosis, hypokalemia, hypoalbuminemia. The patient was under general anesthesia with epidural analgesia. The surgery rans for 5 hours. Postoperative patients were transferred to post-anesthesia care unit (PACU) and EC measurements were carried out before and after postoperative hemodynamic management. Changes in cardiac output seen by EC measurements by considering lactate values as microcirculation parameters can be used to predict hemodynamic responses to fluids.